FROM THE BLACKBOARD TO THE VIRTUAL CLASSROOM: CHILDREN’S RIGHTS TOMORROW - Ganibaeva Shahnoza (Modern American Journals, 2025)
This research article explores the transformation of educational environments from traditional physical classrooms to virtual spaces, emphasizing the evolving framework of children’s rights in digital education.
Keywords: Children’s rights; digital education; virtual classrooms; United Nations Convention on the Rights of the Child; digital privacy; online safety